Carcinoma of Pulmonary Squamous Cells with Small Intestine Metastasis in a Cat - Sousa Barbosa, Francisca Maria; dos Santos, José de Jesus Cavalcante; de Gois, Daniela Dantas; da Costa Lima, Raquel; de Sousa, Maria de Fátima; da Silva Lima, Luiz Henrique; de Souza e Silva, Amabile Arruda; de Lucena, Ricardo Barbosa (Acta Scientiae Veterinariae, 2019)
Background: Primary lung tumors in cats are mainly classified into adenocarcinoma arising from peripheral pulmonary epithelium and, in a smaller number of cases, into adenosquamous or squamous carcinoma, bronchioloalveolar carcinoma, and carcinoid tumor. There are few reports in the international literature describing lung cancer metastasis to visceral organs in cats, especially with regard to squamous tumors. This report describes the clinical pathological, histological, and immunohistochemical findings of lung squamous cell carcinoma with metastasis to small intestine in a cat. Case:A female, Siamese, unneutered, adult cat presented with an unhealed ulcerative crusted lesion on the left ear, previously diagnosed as squamous cell carcinoma (SCC). Six months later, the cat returned presenting with increased volume in the left pelvic limb and claudication due to severe osteolysis in metatarsal and tarsal bones, as shown in radiographic examinations. The limb was amputated forty day later, but it did not undergo histological examination. The cat died fourteen days after amputation and underwent necropsy. Macroscopically, significant changes were observed in the small intestine, including serous segmental necrotizing and hemorrhagic lesion with luminal stenosis and corrugation of mucous surface, which was covered with a fibrinopurulent pseudomembrane. Palpation of lung parenchyma showed small firm nodules. There was an ulcerative crusted lesion on the left ear. Histopatological examination revealed infiltration of pleomorphic neoplastic epithelial cells disrupting the architecture of small intestine and lung, with pronounced anisocyitosis and anisokaryosis. The neoplastic cells had indistinct borders; their cytoplasm was eosinophilic and pleomorphic and varied from moderate to abundant in amount; and their nuclei were markedly pleomorphic and large, with up to two evident nucleoli and salt-and-paper chromatin. Additionally, numerous keratin pearls and remarkable squamous differentiation were observed. Immunohistochemistry (IHC) was performed with the streptavidin-biotin-peroxidase method using anti-pan-cytokeratin and antivimentin antibodies. Neoplastic cells exhibited strong and uniform cytoplasmatic immunoreactivity for pan-cyitokeratin. Vimentin expression was absent in neoplastic cells but present in the connective tissue associated with the neoplasm. Discussion: Although there are some studies on primary lung squamous cell carcinoma, to the authors’ knowledge, this is the second report describing the metastasis of this tumor to small intestine in a cat. The diagnosis of lung SCC in a cat with metastasis to small intestine was confirmed by histopathological assessment and IHC. Although the amputated limb had not undergone histopathological examination, osteolytic lesions in metatarsal and tarsal bones suggested metastasis from primary lung tumors. The lack of involvement of head lymph nodes shows that cutaneous SCC was not related to lung tumors, because metastasis of this carcinoma always involves regional lymph nodes. Paleness of oral and ocular mucosae suggested anemia or paraneoplastic syndrome, which could not be confirmed because the animal was debilitated at presentation and eventually died. IHC confirmed the epithelial origin of the tumor, as evidenced by the presence of epithelial cells and keratin pearls in the small intestine, thus proving the existence of metastasis.